Effects of endophytic actinomycetes and bradyrhizobium japonicum strains on growth, nodulation, nitrogen fixation and seed weight of different soybean varieties - Khin Myat Soe (2018)
© 2012 Japanese Society of Soil Science and Plant Nutrition. Effects of endophytic actinomycetes and two Bradyrhizobium japonicum (Kirchner 1896) Jordan 1982 strains on growth, nodulation, nitrogen (N) fixation and seed weight of different soybean (Glycine max L. Merr.) varieties from Myanmar (Hinthada), Thailand (SJ5) and Cambodia (DT84) were studied in pot experiments in Thailand. The six treatments consisted of an uninoculated control (T1), a single inoculation with endophytic actinomycetes (Streptomyces sp. strain, P4) (T2), a single inoculation with Bradyrhizobium japonicum strains, USDA110 (T3) or THA7 (T4) and a dual inoculation of P4 with USDA110 (T5) or THA7(T6). Sterile soil was used for cultivation of all treatments under open field conditions, using tap water for irrigation. N2 fixation activity of soybean was evaluated by the relative ureide method using xylem solute from the root bleeding sap at the early pod-fill stage. It was found that the single inoculation of P4 did not show significant effects on nodulation, N2 fixation, shoot dry weight and seed weight at harvest of all soybeans compared with the uninoculated control. In the Hinthada soybean, single inoculation of USDA110 or THA7 increased seed weight while USDA110 improved N2 fixation (P < 0.05). Dual inoculation of USDA110 and P4 showed the highest shoot N accumulation and seed weight among treatments. In the SJ5 soybean, similar trends to Hinthada were shown, although the THA7 and P4 combination showed the highest shoot N accumulation and seed weight. On the other hand, in the DT84 soybean, there were no significant differences of N2 fixation and seed weight between USDA110 and THA7 (both single and dual inoculation). In conclusion, dual inoculation of endophytic actinomycetes strain P4 may increase the nodulation and nitrogen fixation in some varieties; however, it is not effective for other varieties.